2020
DOI: 10.1016/j.jretconser.2020.102224
|View full text |Cite
|
Sign up to set email alerts
|

Unusual purchasing behavior during the early stages of the COVID-19 pandemic: The stimulus-organism-response approach

Abstract: During the COVID-19 pandemic, unusual consumer behavior, such as hoarding toilet paper, was reported globally. We investigated this behavior when fears of consumer market disruptions started circulating, to capture human behavior in this unique situation. Based on the stimulus-organism-response (S-O-R) framework, we propose a structural model connecting exposure to online information sources (environmental stimuli) to two behavioral responses: unusual purchases and voluntary self-isolation. To test the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
667
2
46

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 680 publications
(737 citation statements)
references
References 65 publications
22
667
2
46
Order By: Relevance
“…Consumers hesitate to purchase goods at stationary retailers due to government restrictions and fears of infection [37]. Another study found a positive relation between the intention to self-isolate and unusual buying behavior [38]. A survey exploring consumer behavior in the US before and after the COVID-19 crisis revealed that the pandemic has had an impact on purchasing behaviors, as individuals have significantly increased their online shopping use [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consumers hesitate to purchase goods at stationary retailers due to government restrictions and fears of infection [37]. Another study found a positive relation between the intention to self-isolate and unusual buying behavior [38]. A survey exploring consumer behavior in the US before and after the COVID-19 crisis revealed that the pandemic has had an impact on purchasing behaviors, as individuals have significantly increased their online shopping use [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Los consumidores están acostumbrados a la disponibilidad de una gran variedad de productos que pueden ser adquiridos en varios minoristas (Laato et al, 2020a). La escasez del producto amenaza la libertad de escoger entre ellos.…”
Section: Almacenamiento De Bienesunclassified
“…El acaparamiento, ya sea como respuesta a un miedo a quedarse sin producto o como instrumento de generar ganancias económicas, debe ser estudiado para poder tomar acciones que permitan estar mejor preparado. Esto en caso que se den situaciones similares a futuro como un rebrote del coronavirus (Laato et al, 2020a). En Auckland, Nueva Zelandia se dio un aumento del 40% en compras en el supermercado, comparado al 2019.…”
Section: Almacenamiento De Bienesunclassified
See 1 more Smart Citation
“…Y aún con la evidencia de su efectividad, la población se muestra reacia a la adopción de las medidas de seguridad puesto que se trastocan de manera abrupta los estilos de vida, la movilidad, la estabilidad económica y familiar, y en general las relaciones del día a día (Healy, 2020). Aunado a ello, existen factores como la sobreexposición a contenidos en internet (falsos y verdaderos) que provocan efectos positivos, pero también episodios de crisis y de ciber-condria (Laato, Islam, Farooq y Dhir, 2020), de manera que, aún con la…”
Section: Introductionunclassified